Stakeholders’ Level of Awareness, Understanding, and Acceptability of CBSUA Vision, Mission, and Program Goals and Objectives of the Master of Science in Disaster Risk Management - Rene N. Rabacal; Yolanda S. Agawa (East Asian Journal of Multidisciplinary Research, 2023)
The study assessed the stakeholders’ level of awareness, understanding, and acceptability of the Central Bicol State University of Agriculture (CBSUA) vision, mission, and program goals and objectives of the Master of Science in Disaster Risk Management (MSDRM) program of the University. The project used a descriptive-evaluative research design. A researcher-made survey questionnaire was administered among the 95 stakeholder respondents through Google forms. The findings of the study revealed that the majority of the respondent-stakeholders are aware of the MSDRM Objectives; the sources of information on the CBSUA PVMGO, Graduate School (GS) Goals, and MSDRM program are the CBSUA website, bulletin boards on the CBSUA premises, and from students studying at CBSUA; all of the respondents-stakeholders highly understood the vision and mission of the University, the GS goals and the objectives of the program; and the respondents highly accepted the vision and mission of the University, the GS goals, and the MSDRM objectives.